The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/molecules24162936
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Degree of Maturity of Walnuts (Juglans regia L.) and Their Variety on the Antioxidant Potential and the Content of Tocopherols and Polyphenols

Abstract: The aim of the study was to characterize the antioxidant properties; establish the profile of polyphenolic compounds and evaluate the content of tocopherols in walnuts of three varieties (Leopold; Apollo; Resovia) differing in the degree of maturity (harvest date). The profile of polyphenolic compounds was established by UPLC-PDA-ESI-MS. The content of tocopherols was determined by HPLC-FLD. It was found that the content of dry matter and fat increased and the antioxidant properties decreased with the maturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 39 publications
7
25
1
7
Order By: Relevance
“…Even so, the literature lacks information on the influence of the degree of maturity on the fat content of hazelnuts. Among data from Pycia et al [10], a similar correlation was found between the fat content of walnut fruits and their harvest date. The quoted authors indicate that the content of this ingredient increased with the ripening and in walnuts harvested in September it was on average 22.64 g/100 g d.m.…”
Section: Fat Contentsupporting
confidence: 58%
See 4 more Smart Citations
“…Even so, the literature lacks information on the influence of the degree of maturity on the fat content of hazelnuts. Among data from Pycia et al [10], a similar correlation was found between the fat content of walnut fruits and their harvest date. The quoted authors indicate that the content of this ingredient increased with the ripening and in walnuts harvested in September it was on average 22.64 g/100 g d.m.…”
Section: Fat Contentsupporting
confidence: 58%
“…The analysis of polyphenolic compounds profile was performed by ultra-efficient liquid chromatography coupled with a mass detector (UPLC-PDA-ESI-MS) (Waters, Micromass, Manchester, UK) [10,16,17]. The study used the Aquity liquid chromatograph (Waters, Micromass, Manchester, UK), coupled with a photodiode array (PDA) and a tandem quadrupole detector (TQD).…”
Section: Analysis Of Profile and Content Of Polyphenolsmentioning
confidence: 99%
See 3 more Smart Citations